Understanding "Understanding": Industrial Relations Research and Policy in Canada from 1969 to 1984...and Beyond - Arthurs, H.W. (Relations industrielles / Industrial Relations, 1984)
This paper is the H.D. Woods Memorial Lecture presented at the 1984 Annual Meeting of the Canadian Industrial Relations Association, Guelph, Ontario.